Autonomic cardiovascular control and sports classification in Paralympic athletes with spinal cord injury. Issue 2 (16th January 2017) - West, Christopher R.; Krassioukov, Andrei V.
Abstract: Purpose To investigate the relationship between the classification systems used in wheelchair sports and cardiovascular function in Paralympic athletes with spinal cord injury (SCI).Methods 26 wheelchair rugby (C3–C8) and 14 wheelchair basketball (T3‐L1) were assessed for their International Wheelchair Rugby and Basketball Federation sports classification. Next, athletes were assessed for resting and reflex cardiovascular and autonomic function via the change (delta) in systolic blood pressure (SBP) and heart rate (HR) in response to sit-up, and sympathetic skin responses (SSRs), respectively.Results There were no differences in supine, seated, or delta SBP and HR between different sport classes in rugby or basketball (all p  > 0.23). Athletes with autonomically complete injuries (SSR score 0‐1) exhibited a lower supine SBP, seated SBP and delta SBP compared to those with autonomically incomplete injuries (SSR score >1; all p  < 0.010), independent of sport played. There was no association between self-report OH and measured OH (χ 2  =   1.63, p  = 0.20).Conclusion We provide definitive evidence that sports specific classification is not related to the degree of remaining autonomic cardiovascular control in Paralympic athletes with SCI. We suggest that testing for remaining autonomic function, which is closely related to the degree of cardiovascular control, should be incorporated into sporting classification. Implications for Rehabilitation: Spinal cord injury is a debilitating condition that affects the function of almost every physiological system. It is becoming increasingly apparent that spinal cord injury induced changes in autonomic and cardiovascular function are important determinants of sports performance in athletes with spinal cord injury. This study shows that the current sports classification systems used in wheelchair rugby and basketball do not accurately reflect autonomic and cardiovascular function and thus are placing some athletes at a distinct disadvantage/advantage within their respective sport.